Insulin stimulation of Akt/PKB phosphorylation in the placenta of preeclampsia patients - Ferreira, Gustavo Dias; Orcy, Rafael Bueno; Martins-Costa, Sérgio Hofmeister; Ramos, José Geraldo Lopes; Brum, Ilma Simoni; Corleta, Helena von Eye; Capp, Edison (São Paulo Medical Journal, 2011)
CONTEXT AND OBJECTIVE: Preeclampsia is a multi-systemic disease and one of the most frequent severe health problems during pregnancy. Binding of insulin triggers phosphorylation and activates cytoplasmic substrates such as phosphatidylinositol 3 kinase (PI3K). Phosphorylation of membrane phosphoinositide 2 (PIP2) to phosphoinositide 3 (PIP3) by PI3K starts Akt/PKB activation. Defects in phosphorylation of the insulin receptor and its substrates have an important role in insulin resistance. Studies have shown that insulin resistance is associated with preeclampsia and its pathophysiology. The aim here was to investigate insulin stimulation of the Akt/PKB pathway in the placenta, in normal and preeclampsia parturients. DESIGN AND SETTING: Cross-sectional study in a tertiary public university hospital. METHODS: Placentas were collected from 12 normal and 12 preeclampsia patients. These were stimulated and analyzed using Western blot to quantify the Akt/PKB phosphorylation. RESULTS: The insulin stimulation was confirmed through comparing the stimulated group (1.14 ± 0.10) with the non-stimulated group (0.91 ± 0.08; P < 0.001). The phosphorylation of Akt/PKB did not differ between the placenta of the normal patients (1.26 ± 0.16) and those of the preeclampsia patients (1.01 ± 0.11; P = 0.237). CONCLUSIONS: In vitro insulin stimulation of the human placenta has been well established. There was no difference in Akt/PKB phosphorylation, after stimulation with insulin, between placentas of normal and preeclampsia patients. Nevertheless, it cannot be ruled out that the Akt/PKB signaling pathway may have a role in the pathophysiology of preeclampsia, since the substrates of Akt/PKB still need to be investigated.